Professional Safety in the daily life of primary health care: grounded theory - Mariana Delfino Gontijo; Amanda Tainara Souza Freitas; Amanda Ferreira de Faria Maia; Virgínia Junqueira de Oliveira; Selma Maria da Fonseca Viegas (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to understand Professional Safety in daily life in Primary Health Care. Methods: this is a study on the Grounded Theory method and the Symbolic Interactionism theoretical framework with 82 health professionals. Results: it presents the category "Professional Safety in Daily Life in Primary Health Care: a Grounded Theory" and two subcategories determining and conditioning Professional Safety in PHC: professional training, infrastructure, support and technical responsibility; Professional Safety: physical protection, psychological support, distress and feelings reveal the (un)safe conditions. Professional Safety is mentioned in several dimensions that include professionals' knowledge, decision-making skills, the practice of the profession and what regulates it, the structure and organization of the Unified Health System and services, permanent education. It presents the context of primary care and the factors that impact an (unsafe) work. Final considerations: this study contributes to reflect on Professional Safety to strengthen safety culture in Primary Health Care.